Synthesis and anti-hepatocellular carcinoma activity of aminopyridinol-sorafenib hybrids - Bhuwan Prasad Awasthi; Prakash Chaudhary; Diwakar Guragain; Jun-Goo Jee; Jung-Ae Kim; Byeong-Seon Jeong (Taylor & Francis Group, 2021)
Sorafenib is recommended as the primary therapeutic drug for patients with hepatocellular carcinoma. To discover a new compound that avoids low response rates and toxic side effects that occur in sorafenib therapy, we designed and synthesized new hybrid compounds of sorafenib and 2,4,5-trimethylpyridin-3-ols. Compound 6 was selected as the best of 24 hybrids that inhibit each of the four Raf kinases. The anti-proliferative activity of 6 in HepG2, Hep3B, and Huh7 cell lines was slightly lower than that of sorafenib. However, in H6c7 and CCD841 normal epithelial cell lines, the cytotoxicity of 6 was much lower than that of sorafenib. In addition, similar to sorafenib, compound 6 inhibited spheroid forming ability of Hep3B cells in vitro and tumour growth in a xenograft tumour model of the chick chorioallantoic membrane implanted with Huh7 cells. Compound 6 may be a promising candidate targeting hepatocellular carcinoma with low toxic side effects on normal cells.